DYNAMICS OF POSTURAL REGULATION OF PATIENTS WITH TRAUMATIC BRAIN INJURY INFLUENCED BY RESTORATIVE TREATMENT - Ляховецкая, Вера Витальевна; Коновалова, Нина Геннадьевна (Medicine in Kuzbass, 2020)
Subject. Postural regulation of patients with traumatic brain injury. Objective – to evaluate the influence of restorative treatment on the dynamics of postural regulation of patients with traumatic brain injury. Methods. Altogether, 82 patients were observed in the late recovery period of traumatic brain injury. All patients underwent a clinical neurological examination and computer stabilometrics at the beginning and end of the course of restorative treatment. Results. The area of the statokinesiogram, deviations in the frontal plane and the work of patients is larger than when standing healthy people, the stability factor is lower. Closing the eyes makes the vertical position less stable. The Romberg Coefficient is 266. After a course of restorative treatment, a decrease in the area of the statokinesiogram, deviations in the frontal plane, and work were observed. The most significant changes occurred when standing with eyes closed. The Romberg coefficient decreased to 141 and became comparable to that of healthy people standing. Field of application: neurology, restorative medicine. Conclusion. Maintaining the vertical posture of patients with traumatic brain injury in the late recovery period requires more energy than in healthy persons. Standing is provided by increasing deviations and reducing the frequency of vibrations in the frontal plane. In the vertical plane, deviations, on the contrary, tend to decrease, and the frequency of fluctuations tend to increase. These changes are typical for all patients, but they are more manifested in individuals with tetraplegia. The parameters of the stabilogram of patients with left-sided hemiparesis are closest to those of healthy people. As a result of a course of restorative treatment, the stability of the vertical posture increases, and the energy cost decreases when standing with open eyes, and, to a greater extent, when standing with closed eyes.